Kearifan Lokal “Wayang Golek” Sebagai Media Pembelajaran Di Era Abad-21 - Zulfah, Zulfah; Sonia, Sonia (Bestari, 2022)
Media is one component that is the key to success in the teaching and learning process to achieve learning objectives. In the 21st century, it is often identified with the development of industry 4.0, where technological sophistication is advancing so that it can become a threat to the disappearance of local culture. The purpose of this study was to describe the implementation of wayang golek learning media in its role for learning achievement and active learning of students in the exemplary material of the Prophet Ibrahim a.s and Prophet Ismail a.s in the subject of Islamic Religious Education. The type of research used is research and development (R&D) using the Four-D (4D) model. The study population was students of SD at Bintan with the selected sample being class III SDN 001 Teluk Bintan. Collecting data through observation sheets, media and instrument validation, learning achievement questions and learning activity observation sheets. The results of the media trial, the value of learning achievement is seen from its completeness through the KKM and the value of student activity through observation during learning. Based on the trial, it was found that 75% of the students were complete in learning with scores above the KKM and the students seemed to be very active in participating in learning with the wayang golek media.